Elevated Movement Path Tortuosity in Voluntary Outdoor Ambulation in Community-Dwelling Veterans With a History of Traumatic Brain Injury. Issue 1 (January 2015) - Kearns, William D.; Fozard, James L.; Schonfeld, Lawrence; Scott, Steven; Marshall, Katharine
<x xml:space="preserve">Abstract</x> Objective: In comparison to veterans without a history of traumatic brain injury (TBI), we hypothesized that veterans with past TBI would have slower walking speed and more path tortuosity, TBI symptoms, problems with spatial orientation, and poorer executive function. Setting: Community nonclinical. Participants: Seventeen males (mean age of 37.2 years) reporting prior TBI and 20 non-TBI (mean age of 42.9 years). The number of years separating date of discharge and testing was 10.8 and 15.4 for the TBI and non-TBI groups, respectively. Design: Small 2 groups without random assignment. Main Measures: Brief Traumatic Brain Injury Screen, Trail Making Test-B, Clock Drawing Test, walking speed, and distance and path tortuosity in 30 minutes of voluntary outdoor walking wearing a small Global Positioning Systems recorder. Results: Those with TBI reported 4 Brief Traumatic Brain Injury Screen symptoms versus 0.4 for controls (F = 49.1; df = 1, 35; P < .001) but did not differ on Trail Making Test-B or the Clock Drawing Test. Veterans with TBI walked shorter distances, 2.33 km versus 2.84 km (F = 4.8; df = 1, 35; P < .05), and had greater path tortuosity (fractal D of 1.22 vs 1.15; F = 3.5; df = 1, 35; P < .05) but did not differ on travel speed or time spent walking. Conclusions: Traumatic brain injury has persistent symptomatic effects and significantly affects ambulation and spatial orientation years after the event. These findings corroborate and extend observations linking cognitive impairment and ambulation.